Kebijakan Hukum Dalam Mengurangi Kejahatan Akibat Dampak Kemajuan Komputer - Iskandar Z. Nasibu (JURNAL LEGALITAS, 2009)
Computer crime in global community of internet user public is a thing which can be realized or unconsciously, intertionally or involuntary is done. This thing happened because development of information technology and level of public intelectuality is increases. Keeps abreast of technologi in the computer area, especially in area Information And Communivation technologi (ICT), badness by using computer technology has come up with phase to worry so that law footing to become a real footing that was public required. Law challenged to do regulation, investigation, even where necessary determines penalty system based on justice and rule of law in standing computer technology progress. Kata Kunci: Kebijakan Hukum, Kejahatan, Komputer, Globalisasi,